Four Ways for France to Get Higher Marks - Vérillaud, Francis; Guyot, Manon (International Higher Education, 2021)
The COVID-19 crisis has challenged the French higher education and research system. The government must now engage in sound reforms to make the system sustainable in the long run. The challenge is finding out where to begin and identifying what mechanisms are in place and how to change them.